2019
DOI: 10.5334/aogh.2514
|View full text |Cite
|
Sign up to set email alerts
|

Towards Resilient Health Systems in Sub-Saharan Africa: A Systematic Review of the English Language Literature on Health Workforce, Surveillance, and Health Governance Issues for Health Systems Strengthening

Abstract: Background: Meeting health security capacity in sub-Saharan Africa will require strengthening existing health systems to prevent, detect, and respond to any threats to health. The purpose of this review was to examine the literature on health workforce, surveillance, and health governance issues for health systems strengthening. Methods: We searched PubMed, Science Direct, Cochrane library, CINAHL, Web of Science, EMBASE, EBSCO, Google scholar, and the WHO depository li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 68 publications
1
40
0
Order By: Relevance
“…Health Workforce : This review confirmed existing knowledge about the weak health workforce in much of the African health systems [ 34 ]. Several studies reported poor health worker knowledge of IPTp guidelines/protocols, uncertainty about the safety and efficacy of SP, as well as inadequate and unsystematic supervision [ 20 , 23 , 32 , 33 , 38 , 47 , 57 ].…”
Section: Resultssupporting
confidence: 76%
“…Health Workforce : This review confirmed existing knowledge about the weak health workforce in much of the African health systems [ 34 ]. Several studies reported poor health worker knowledge of IPTp guidelines/protocols, uncertainty about the safety and efficacy of SP, as well as inadequate and unsystematic supervision [ 20 , 23 , 32 , 33 , 38 , 47 , 57 ].…”
Section: Resultssupporting
confidence: 76%
“…Lack of essential aspects that strengthen the health system, such as good health governance and leadership, health surveillance and appropriate health workforce, impended health security. 4 Moreover, food insecurity and hunger prevailed for multiple reasons such as escalating armed conflicts and socio-economic grievances. 5 Some East African countries suffer significantly from locust invasions, while other pests affect the Sahel region and southern Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Countries N The WHO defines health systems as "all organizations, people and actions whose primary intent is to promote, restore, or maintain health" [21]. In LRCs, these systems have long been weak and deficient in most aspects of healthcare delivery and therefore, there is persistent need to evaluate health system challenges at all levels [22]. Health security is a crucial public health issue.…”
Section: Regionmentioning
confidence: 99%